Creating and Teaching Science Lessons in K–12 Schools Increases Undergraduate Students’ Science Identity - Jennifer A. A. Gubbels (American Society for Microbiology, 2018)
Success and persistence in the life sciences is influenced by a student’s self-efficacy, sense of belonging, and science identity. It has already been demonstrated that outreach experiences and service learning by graduate students in K–12 schools aid in the graduate students’ confidence and intrinsic satisfaction. Others have shown the importance of engaging scientists in outreach activities, both for the benefit of the K–12 student and as a way to engage scientists with the community. We predicted it would also be beneficial for undergraduates to engage in service-learning activities during their coursework because working with K–12 students would solidify their scientific identity and sense of belonging while deepening their understanding of the course content. Consequently, we implemented service projects in our upper-level molecular biology and human physiology courses at a primarily undergraduate institution that focuses on five core values: Christian, Liberal Arts, Excellence, Community, and Service. Outcomes such as the undergraduate students’ value of service, confidence in their knowledge of course content, ability to create effective lesson plans, and science identity were measured using anonymous surveys. Overall, students reported that they highly valued and enjoyed this unique experience. This type of activity could be used to increase future scientists’ awareness of synergistic activities such as academic service and of the joy found in such activities. Future plans include measuring the effects on the participating high school and elementary school students and visiting schools with a high proportion of students from underserved populations.